2012
DOI: 10.1111/j.1755-0238.2012.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein removal from a Chardonnay juice by addition of carrageenan and pectin

Abstract: Backgrounds and Aims:Bentonite is commonly added to white wines to remove the grape proteins responsible for haze formation. Despite being effective, this technique has drawbacks; thus, new solutions are desirable. The ability of carrageenan and pectin to remove heat-unstable grape proteins, and the impact that such addition has on the physicochemical and sensorial profile of a wine were assessed. Methods and Results: Carrageenan and pectin were added separately or in combination to a Chardonnay juice prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 17 publications
3
35
1
3
Order By: Relevance
“…Protein stabilisation using polysaccharides, such as carrageenans, is well established in the milk and brewing industries (Duan et al ). Previous reports of the addition of carrageenans to white wine and grape juice for haze stabilisation have shown that they can be effective when added either during wine processing or to the finished wine (Cabello‐Pasini et al , Marangon et al , ). Carrageenans are naturally occurring polysaccharides extracted from red seaweeds of the Rhophyta species (Necas and Bartosikoya ) and are therefore a potential renewable heat‐stabilising agent.…”
Section: Introductionmentioning
confidence: 99%
“…Protein stabilisation using polysaccharides, such as carrageenans, is well established in the milk and brewing industries (Duan et al ). Previous reports of the addition of carrageenans to white wine and grape juice for haze stabilisation have shown that they can be effective when added either during wine processing or to the finished wine (Cabello‐Pasini et al , Marangon et al , ). Carrageenans are naturally occurring polysaccharides extracted from red seaweeds of the Rhophyta species (Necas and Bartosikoya ) and are therefore a potential renewable heat‐stabilising agent.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 According to Figure 1(b), under optimum conditions, the protein recovery rate of 70% for carrageenan was significantly higher than those of guar, chitosan, and alginate with the values of 49%, 53%, and 55%, respectively. The highest recovery rate for carrageenan might have resulted from its strong negative charge and combined sites, such as its sulfate and hydroxide groups (Marangon et al, 2012). At the same time, the lower recovery rates for alginate, guar gum, and A c c e p t e d M a n u s c r i p t chitosan were because of their weak charge groups: carboxyl groups, hydroxide groups, and amino groups, respectively.…”
Section: Effect Of Ph On Coagulation Performancementioning
confidence: 98%
“…In addition, the need for a stability test that does not rely on heat has increased after the proposal of alternative stabilisation methods such as flash pasteurisation in combination with enzymes (Moreno-Arribas andPolo 2005, Marangon et al 2012a,b) and polysaccharide fining (Cabello-Pasini et al 2005, Vincenzi et al 2005, Marangon et al 2012a. Wines treated with these two methods may fail the conventional heat test (due to the presence of proteins not associated with haze formation) despite being free of haze-forming proteins such as chitinases and TLPs.…”
Section: Protein Instabilitymentioning
confidence: 99%